Saúde mental na percepção de engenheiros de produção recém-formados: desafios no mercado de trabalho - Villela, Mariana Figueiredo Junqueira (Universidade Federal de São Carlos, 2023)
Concern about mental health has been growing by the part of companies and society due to the increase in diagnoses of work-related mental disorders. The present research sought to evaluate and understand the mental health of recent graduates of the manufacturing engineering course at a public university in the State of São Paulo. For this, questionnaires and interviews were applied to collect the perceptions of these young workers. The results made it possible to identify the main themes that involve this study and the main frustrations of the interviewees in this regard. The main results indicated: aggravation of symptoms, difficulty disconnecting from work, many work leaves, feelings of discouragement, exacerbated self-demand and insecurity, lack of autonomy, excesses of responsibility and workload, factors that directly interfere with the quality of work, health, personal life and professional development of these young minds. It was concluded that it is urgent to implement a safe environment for discussing the issue of mental health at work, in which the members of a company feel welcomed and listened to, associated with the inclusion of benefits aimed at facilitating access to psychological treatments and several others which aims at mental well-being, thus preventing further illness and making the most of all available human potential.
Mental health in the perception of newly graduated production engineers: challenges in the job market
Keywords: Transtornos mentais; Recém-formados; Trabalhadores; Trabalho; Engenheiros; Mental disorders; Newly graduate; Workers; Work; Engineers; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS